MdFLP enhances drought tolerance by regulating MdNAC019 in self-rooted apple stocks. (August 2022) - Wang, Zenghui; Li, Jialin; Yang, Xuemei; Hu, Yanli; Yin, Yanlei; Shen, Xiang
Abstract: Self-rooted apple stocks are widely used for the production of apples worldwide. However, self-rooted apple stocks are weak due to shallow roots and poor grounding, resulting in poor drought resistance. Therefore, it is essential to understand the molecular mechanisms to develop self-rooted apple stock cultivars with drought resistance. We reported that MdFLP, an R2R3-MYB transcription factor, directly binds to the promoter of MdNAC019, activating its transcription and consequently enhancing drought tolerance in self-rooted apple stocks. In addition, MdFLP indirectly activates the transcriptional expression of abiotic stress-related genes, namely, MdERF6 and MdZAT10 . The plants overexpressing MdFLP displayed stronger drought tolerance, whereas MdFLP- RNAi plants showed weak drought tolerance compared with non-transgenic "Gala" plants, indicating that MdFLP regulates drought tolerance in self-rooted apple stocks. Altogether, we believe that our findings provide novel insights into the functions of MdFLP in the regulation of drought tolerance in self-rooted apple stocks. Highlights: We reported that MdFLP, an R2R3-MYB transcription factor, directly binds to the promoter of MdNAC019, activating its transcription and consequently enhancing drought tolerance in self-rooted apple stocks. In addition, MdFLP indirectly activates the transcriptional expression of abiotic stress-related genes, namely, MdERF6 and MdZAT10 . The plants overexpressing MdFLP displayed stronger drought tolerance, whereas MdFLP- RNAi plants showed weak drought tolerance compared with non-transgenic "Gala" plants, indicating that MdFLP regulates drought tolerance in self-rooted apple stocks. Altogether, we believe that our findings provide novel insights into the functions of MdFLP in the regulation of drought tolerance in self-rooted apple stocks.